(NkOGERENTNOE R\LEEWSKOE RASSEQNIE MESSBAU\ROWSKOGO IZLU^ENIQ (B/s - (NzOLOTOQBKO(B, (N|MILX wULXFOWI^s; (NiOLIN(B, (NeWGENIJ mIHAJLOWI^s; (N{WARC(B, (Nk(B.(Nk(B.s ((NrIGA (B:s (NzINATNE(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 162-171 (206 (NNAZW(B.)s
(Nan lATWIJSKOJ ssr(B, (NiN(B-(NT FIZIKIs
Keywords: (NmESSBAU\RA \FFEKTs